Improving approaches to determining the cost of engineering services in construction - Demianenko О. О. (Ways to Improve Construction Efficiency, 2019)
The emergence of a new profession in civil engineering in 2017 in Ukraine calls for a number of tasks to be solved in defining its rights and responsibilities, tasks and functions, and requires the development of a methodological approach to defining engineering services in construction. Currently, the problem is to justify the amount of costs that can be provided by a consolidated estimate for the maintenance of the service of the Consulting Engineer in the limit of 3.5% of Chapters 1-9, forming a standard list of services. The purpose of the study is to review the existing approaches to the formation of the cost of engineering services in construction, to analyze the international experience, regulatory and legal framework, to determine the list of factors that influence the cost of assessing the technical condition of objects. The article discusses approaches to determining the cost of engineering services in construction. The directions of their improvement are determined at all stages of the object’s life cycle, as an example of certain types of engineering services. As a result of the analysis of existing approaches to determining the cost of engineering services, it is established that the main approaches to determining the cost are time and interest rate. There are a number of regulatory and technical documents in Ukraine governing the determination of the cost of certain types of services. The analysis of normative documents governing the determination of the cost of works on the assessment of the technical condition, allowed to determine the list of factors that influence the cost of the assessment of the technical condition of the object (on the example of collectors) and to determine the directions of improvement of such assessment. Improving approaches in Ukraine involves the need to streamline the services of a consulting engineer at various stages of the facility’s life cycle, and to determine the appropriate prevailing pricing approach. Development of the necessary aggregated labor cost and interest rates to determine the services of a consulting engineer